Agglutinin-Like Sequence (ALS) Genes in the Candida parapsilosis Species Complex: Blurring the Boundaries Between Gene Families That Encode Cell-Wall Proteins - Oh, Soon-Hwan; Smith, Brooke; Miller, Andrew N.; Staker, Bart; Fields, Christopher; Hernandez, Alvaro; Hoyer, Lois L. (Frontiers in Microbiology, 2019)
The Agglutinin-Like Sequence (Als) proteins are best-characterized in Candida albicans and known for their role in adhesion of the fungal cell to host and abiotic surfaces. ALS sequences are often misassembled in whole-genome sequence data because each species has multiple ALS loci that contain similar sequences, most notably tandem copies of highly conserved repeated sequences. The Candida parapsilosis species complex includes Candida parapsilosis, Candida orthopsilosis, and Candida metapsilosis, three distinct but closely related species. Using publicly available genome resources, de novo genome assemblies, and laboratory experimentation including Sanger sequencing, five ALS genes were characterized in C. parapsilsosis strain CDC317, three in C. orthopsilosis strain 90-125, and four in C. metapsilosis strain ATCC 96143. The newly characterized ALS genes shared similar features with the well-known C. albicans ALS family, but also displayed unique attributes such as novel short, imperfect repeat sequences that were found in other genes encoding fungal cell-wall proteins. Evidence of recombination between ALS sequences and other genes was most obvious in CmALS2265, which had the 5’ end of an ALS gene and the repeated sequences and 3’ end from the IFF/HYR family. Together, these results blur the boundaries between the fungal cell wall families that were defined in C. albicans. TaqMan assays were used to quantify relative expression for each ALS gene. Some measurements were complicated by the assay location within the ALS gene. Considerable variation was noted in relative gene expression for isolates of the same species. Overall, however, there was a trend toward higher relative gene expression in saturated cultures rather than younger cultures. This work provides a complete description of the ALS genes in the C. parapsilosis species complex and a toolkit that promotes further investigations into the role of the Als proteins in host-fungal interactions.